2011
DOI: 10.1101/lm.2095811
|View full text |Cite
|
Sign up to set email alerts
|

Different compartments of apical CA1 dendrites have different plasticity thresholds for expressing synaptic tagging and capture

Abstract: The consolidation process from short-to long-term memory depends on the type of stimulation received from a specific neuronal network and on the cooperativity and associativity between different synaptic inputs converging onto a specific neuron. We show here that the plasticity thresholds for inducing LTP are different in proximal and distal compartments of apical dendrites. In addition, we show interactions between the proximal and distal compartments of the apical dendrites by providing evidence that even a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…with the concept that there are two contributors to the plasticity threshold essential for the effective coding of information from multiple inputs (11,12). First, information must be encoded by means of a change in synaptic weights, and synaptic tags must be set.…”
Section: S1mentioning
confidence: 99%
“…with the concept that there are two contributors to the plasticity threshold essential for the effective coding of information from multiple inputs (11,12). First, information must be encoded by means of a change in synaptic weights, and synaptic tags must be set.…”
Section: S1mentioning
confidence: 99%
“…radiatum) and the basal dendrites in the stratum oriens (str. oriens).Studies of long-term potentiation (LTP) in the hippocampal slices both in vitro and in vivo have shown that the threshold for inducing LTP is lower in basal dendrites in comparison to apical dendrites (Kaibara and Leung 1993;Leung and Shen 1995;Sajikumar et al 2007;Stramiello and Wagner 2010;Sajikumar and Korte 2011a). The CA1 region receives a variety of neuromodulatory inputs including the dopaminergic, cholinergic, and noradrenergic pathways (Otmakhova and Lisman 2000;Leung et al 2003), and the distributions of these neuromodulatory inputs are not uniform.…”
mentioning
confidence: 99%
“…In the distal basal dendrites, synaptic potentiation occurs only when synaptic activation (which is strong enough to evoke an NMDA spike) is paired with BDNF application (Gordon et al 2006). Even within the apical dendrites, the plasticity thresholds for inducing LTP and LTD are different in distal and proximal regions (Parvez et al 2010;Sajikumar and Korte 2011a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Allow 20 min for the slices to recover. Test the pathway independence with a paired-pulse facilitation protocol 27,28 .…”
Section: Recording Of Ca3-ca1 Synaptic Responsesmentioning
confidence: 99%